IMPACT OF GOVERNMENT SPENDING AND FOREIGN INVESTMENT ON EXPORTS, IMPORTS, AND ECONOMIC GROWTH IN INDONESIA - maolana, agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Economic integration have an impact on increasing trade volume and production output in various countries. Likewise, the ease of capital mobility between countries, makes investment not only rely on capital derived from domestics, but can come from foreign direct investment. This study used time series data during the 1980-2019 . The analysis model used is multiple linear regression using, by first testing classical assumptions so that the regression results are Unbias. The results showed that foreign investment, government spending, and economic openness can significantly increase export, import, and economic growth. Furthermore, the rupiah exchange rate , which is depreciating against the US dollar, can increase export growth and reduce Indonesia's import growth. Meanwhile, higher inflation can cause a significant decline in export and import growth, but an insignificant decline for Indonesia's economic growth.